Marxism and the State - Wetherly, P. author. aut Link
XIII, 247 p.
Keywords: Paul Wetherly provides a restatement and defence of the classical Marxist theory of the state, developing an analytical approach that draws on G.A. Cohen's functional interpretation of Marx's theory of history. Instrumentalist and structuralist arguments are conceived as related causal mechanisms within the functional approach, and the principle of economic determination is shown to be consistent with the relative autonomy of the state as an institution with its own interests and capacities. This old-fashioned interpretation is defended against rival approaches within contemporary Marxism.